RTHP-32. RECONSIDERING THE PROGNOSTIC IMPACT OF AGE, GRADE, AND EXTENT OF RESECTION ON CLINICAL OUTCOMES OF 1p/19q CODELETED OLIGODENDROGLIOMAS AFTER RADIATION THERAPY: A MULTI-INSTITUTIONAL REPORT. (5th November 2018) - Lin, Alexander; Kane, Liam; Molitoris, Jason; Smith, Deborah; Badiyan, Shahed; Wang, Tony; Kruser, Tim; Huang, Jiayi
Abstract: OBJECTIVE: Age, grade, and extent of resection (EOR) are key factors to guide the treatment of gliomas. This multi-institutional study examines their prognostic impact on the favorable subset of molecularly-defined oligodendroglioma after definitive radiation therapy (RT). METHODS: Grade 2–3 oligodendroglioma patients treated with RT with or without chemotherapy from 2000–2017 at four tertiary academic cancer centers were retrospectively reviewed. Eligible patients were required to have 1p/19q codeletion as well as defined grade and EOR within 12 months of RT. Progression-free survival (PFS) and overall survival (OS) rates were determined using Kaplan-Meier analyses. Cox regression analysis was used to identify factors associated with worse PFS and OS. RESULTS: One hundred sixty-eight patients were identified with median follow-up of 43 months (0.5–200). Median age was 46 (23–80), 79(47%) had gross-total resection, 121(72%) were grade 3; 106(63%) received adjuvant RT and temozolomide (TMZ), 26(15%) received adjuvant RT and procarbazine/lomustine/vincristine (PCV), 18(11%) received adjuvant RT alone, and 18(11%) received prior chemotherapy before salvage surgery and RT. Overall, the 10-year PFS and OS were 52% and 65%, respectively. On multivariable analysis, lower KPS (HR:0.96, 95% CI:0.93–0.99), gliomatosis (HR:195, 95% CI:16–2340), and prior chemotherapy (HR:2.2, 95% CI:1.04–4.7) were the only significant factors associated with worse PFS; notably, age, grade, and EOR were not significant for PFS. In a subset of 146 patients excluding those with gliomatosis and prior chemotherapy, age >40, grade 3, subtotal resection, TMZ chemotherapy, and lower RT dose were not associated with worse PFS or OS rates (all p >0.05). CONCLUSIONS: Oligodendrogliomas with 1p/19q codeletion have favorable outcomes after RT, except those with gliomatosis or prior chemotherapy exposure. Traditional prognostic factors of age >40, EOR, and grade do not appear to reliably risk stratify these patients after adjuvant RT. Their use to guide treatment selection may need to be revisited.